KONTRIBUSI PANJANG LENGAN, KEKUATAN OTOT LENGAN DAN DAYA LEDAK LENGAN TERHADAP KEMAMPUAN TOLAK PELURU GAYA MEMBELAKANGI PADA SISWA SMP NEGERI 6 KOTABARU - M Imran Hasanuddin (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2018)
This research is a quantitative descriptive study that uses a "correlational" research design. This study aims to find out: (1) Is there a contribution of the length of the arm with the ability to repel the force back to the male students of SMP Negeri 6 Kotabaru, (2) Is there a contribution of arm strength with a shot-force ability back to the male students of Kotabaru State Middle School 6, (3) Is there a contribution of arm explosive power with repelling force to the male students of SMP Negeri 6 Kotabaru (4) Is there a contribution of arm length, arm strength, and arm explosive power together with the ability to repel the force back to students son of Kotabaru Middle School 6. The population is male students of Kotabaru Middle School 6. The sample used was 49 male students of SMP Negeri 6 Kotabaru. The technique of determining the sample is by random selection by lottery (Simple Random Sampling). The data analysis technique used was descriptive analysis and inferential analysis through the SPSS 22 program at a significance level of 0.05. The results showed that; (1) Is there a contribution of the length of the arm to the force of repelling force back to the male students of SMP Negeri 6 Kotabaru, with a value (r) of 0.641 (Pvalue <Î± 0.05); (2) Is there a contribution of arm strength with a force repelling force back to the male students of Kotabaru Middle School 6, with a value (r) of 0.434 (Pvalue <Î± 0.05); (3) Is there a contribution of arm explosive power with the force of repelling force back to the male students of Kotabaru Middle School 6, with a value (r) of 0769; and (4) Is there a contribution of arm length, arm strength, and arm explosive power together with the repelling force of the back to the male students of SMP Negeri 6 Kotabaru, with an R value of 0.811 (Pvalue <Î± 0.05); and the Fcount value is 28,721. Keywords: arm length, arm strength, arm dayaled, bullet repelling ability